2013
DOI: 10.1111/resp.12078
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in allergic airway remodelling and immunoglobulin production in mouse model of asthma

Abstract: These results indicate that female mice experience more airway remodelling compared with male mice. These results suggest the involvement of sex hormones and gender differences in cellular functions in airway remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 37 publications
6
59
0
9
Order By: Relevance
“…It had been proven that VAS positively correlates with the Rhinoconjunctivitis Quality of Life Questionnaire global score and could be used for the quantitative evaluation of the severity of AR. 13 In this study, we found a statistically significant correlation between the grading of the severity (IM, PM, and IMS to PMS) and VAS scores (Spearman r ϭ 0.263; p Ͻ 0.001). The results correspond to the findings that Bousquet reported previously.…”
Section: Discussionmentioning
confidence: 74%
“…It had been proven that VAS positively correlates with the Rhinoconjunctivitis Quality of Life Questionnaire global score and could be used for the quantitative evaluation of the severity of AR. 13 In this study, we found a statistically significant correlation between the grading of the severity (IM, PM, and IMS to PMS) and VAS scores (Spearman r ϭ 0.263; p Ͻ 0.001). The results correspond to the findings that Bousquet reported previously.…”
Section: Discussionmentioning
confidence: 74%
“…However, OVA-challenged females had increased airway remodeling and mucus production compared to male mice in some reports (50, 51), but no differences were found in others (52•). Presence of ovarian hormones during the sensitization phase is required for maximal Th2-mediated airway inflammation in female mice.…”
Section: Role Of Sex Hormones In Airway Inflammation – Summary Of Animentioning
confidence: 84%
“…Because of the gender differences in asthma onset and respiratory symptoms (Hansen et al, 2015;Takeda et al, 2013), we stratified the allele frequencies and genotypes by gender. However, no statistically significant differences in genotype or allele frequency distribution were found for rs2228145 and rs12083537 between patients and controls in either males or females (supporting Tables 1 and 2).…”
Section: The Genotype and Allele Frequency Distributions In Patients mentioning
confidence: 99%